Pengaruh Penerapan Model Pembelajaran Problem Based Learning (PBL) Terhadap Hasil Belajar Siswa pada Mata Pelajaran Informatika di Kelas X Fase E SMAN 1 Hiliran Gumanti - Januamita, Meri; Zuliarni, Zuliarni; Anugrah, Septriyan; Rahmayanti, Elsa (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to determine the effect of the implementation of the Problem Based Learning (PBL) model on student learning outcomes in the Informatics subject for grade X Phase E at SMAN 1 Hiliran Gumanti. This type of research is a quasi-experimental study. The sample in this study consisted of 60 students from grade X Phase E. The data collection technique used was a test method. The test instrument was used to collect data on student learning outcomes after applying the Problem Based Learning (PBL) model. Data were analyzed using a t-test statistic with a significance level of 0.05. The results showed that the average score of the experimental class was 83.5, and the average score of the control class was 75.6. The t-test calculation resulted in t_calculated = 3.024, which is greater than the t_table value at the 0.05 significance level, which is 1.671. It can be concluded that the implementation of the Problem Based Learning (PBL) model has a significant effect on student learning outcomes in the Informatics subject for grade X Phase E at SMAN 1 Hiliran Gumanti